Eat, Sleep, Console model for neonatal opioid withdrawal syndrome: a meta-analysis - Chu, Liangliang; Liu, Xiaoyi; Xu, Cuiping (Frontiers in Pediatrics, 2024)
Background The rising incidence of drug abuse among pregnant women has rendered neonatal opioid withdrawal syndrome a significant global health concern. Methods Databases including PubMed, Web of Science, the Cochrane Library, Embase, Elton B. Stephens. Company (EBSCO), China National Knowledge Infrastructure (CNKI), and Wanfang were searched for comparative studies of the Eat, Sleep, Console model vs. traditional assessment tools for neonatal opioid withdrawal syndrome. Two reviewers conducted literature searches, screened according to the inclusion criteria, extracted data, and independently verified accuracy. All meta-analyses were conducted using Review Manager Version 5.4. Results In total, 18 studies involving 4,639 neonates were included in the meta-analysis. The Eat, Sleep, Console model demonstrated superior outcomes in assessing neonatal opioid withdrawal syndrome, significantly reducing the need for pharmacological treatment [risk ratio = 0.44, 95% confidence interval (CI) = 0.34–0.56, P < 0.001], decreasing the length of hospital stay [standard mean difference (SMD) = −2.10, 95% CI = −3.43 to −0.78, P = 0.002], and shortening the duration of opioid treatment (SMD = −1.33, 95% CI = −2.22 to −0.45, P = 0.003) compared to the Finnegan Neonatal Abstinence Scoring System. Conclusions The Eat, Sleep, Console model is more effective than the Finnegan Neonatal Abstinence Scoring System in improving the assessment and management of neonatal opioid withdrawal syndrome.